PENGARUH DISPLIN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK PERKREDITAN RAKYAT DANA MANDIRI BOGOR - Siti Aisyah; Bachtiar Arifudin Husain (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of discipline and work environment on employee performance at PT Bank Perkreditan Rakyat Dana Mandiri Bogor. The method used is quantitative. The sampling technique used saturated sampling and a sample of 55 respondents was obtained. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that discipline has a significant effect on employee performance with the regression equation Y = 13.272 + 0.665X1, the correlation coefficient value obtained is 0.705, meaning that the two variables have a strong level of relationship. The result of the determination or contribution of influence was 0.496 or 49.6%, while the remaining 50.4% was influenced by other factors. Hypothesis testing obtained a calculated t value > t table or (7.228 > 2.006). Thus, H0 is rejected and H1 is accepted. The work environment has a significant effect on employee performance with the regression equation Y = 9.831 + 0.767 The value of determination or contribution of influence is 0.594 or 59.4%, while the remaining 40.6% is influenced by other factors. The left side hypothesis test obtained a value of t count > t table or (8.800 > 2.006). This was strengthened by obtaining a significance of 0.000 < 0.05, thus H0 was rejected and H2 was accepted. Discipline and the work environment simultaneously have a significant effect on employee performance with the equation regression Y = 6.089 + 0.321X1 + 0.539X2. The correlation coefficient value or level of relationship between the independent variable and the dependent variable is 0.657, meaning it has a strong relationship. The value of the coefficient of determination or contribution of influence simultaneously is 65.7% while the remaining 34.3% is influenced by other factors. Hypothesis testing obtained a calculated F value > Ftable or (77.435 > 2.780). Thus, H0 is rejected and H3 is accepted.